TÜRKİYE'NİN TİCARİ HİZMETLER ENDÜSTRİ-İÇİ TİCARETİ: ÜLKEYE ÖZGÜ BELİRLEYİCİLERİN TESPİTİ ÜZERİNE BİR UYGULAMA1 - (:unkn) unknown (My University, 2015)
Bu çalışmanın temel amacı, Endüstri-içi Ticaret Teorisi aracılığıyla Türkiye'nin ticari hizmetler endüstri-içi ticaretinin ülkeye özgü belirleyicilerini tespit etmek, ulaşılan bulguları ticari mallar endüstri-içi ticaretinin ülkeye özgü belirleyicileri ile karşılaştırmaktır. Bulgular, 2005 yılı itibariyle önerilen ülkeye özgü belirleyiciler kümesi içinde en önemli faktörlerin; talep yapılarının benzerliği, ekonomik entegrasyonlara katılım ve ticari işlem maliyetleri olduğunu ortaya koymuştur. Doğrudan yabancı yatırımlar dışındaki tüm değişkenler beklendiği yönde sonuç vermiş, ancak ticari mallar endüstri-içi ticareti açısından tamamlayıcı ve pozitif yönlü olan endüstri-içi ticaret-doğrudan yabancı yatırım girişleri ilişkisi, ticari hizmetler açısından tersine dönmüştür. Türkiye'ye giriş yapan yabancı sermaye, hizmetler ticaretini ikame etmekte ve Türkiye'nin hizmetler endüstri-içi ticaret oranlarını düşürücü etki yapmaktadır.

The main purpose of the study is to identify the country-specific determinants of intra-industry trade in services for Turkey by using the Intra-Industry Trade Theory and then to compare its findings with the country-specific determinants of intra-industry trade in commercial goods. The findings indicated that the most important factors within the country-specific determinants that were suggested as of 2005 were similarity of demand structures, participation in economic integrations, and commercial transaction costs. All factors produced the expected results, except for foreign direct investments; however, the correlation between intra-industry trade and foreign direct investment, which is complementary and positive in terms of intra-industry trade in commercial goods, yielded a reverse outcome for commercial services. Inward foreign direct investments substituted the services trade and had a decreasing effect on the intra-industry trade rates of Turkey in services.
INTRA-INDUSTRY TRADE IN COMMERCIAL SERVICES OF TURKEY: AN EMPIRICAL STUDY FOR THE IDENTIFICATION OF COUNTRY-SPECIFIC DETERMINANTS
Keywords: İktisat; İşletme